Realizing Women’s Rights to Land in the Law - Food; Agriculture Organization of the United Nations (United Nations, 2018)
This publication provides methodological guidance for reporting on Target 5.a of the Sustainable Development Goals, namely to “Undertake reforms to give women equal rights to economic resources, as well as access to ownership and control over land and other forms of property, financial services, inheritance and natural resources, in accordance with national laws.” Progress towards this target is measured through two indicators that focus on ownership and/or control over land. This step-by-step guide on the “how” of reporting and measuring progress on indicator 5.a.2. covers the collection of information on the legal and policy framework, the assessment of each of the proxies, and reporting.